Weber revisited: The protestant ethic and the spirit of nationalism - Felix Kersting; Iris Wohnsiedler; Nikolaus Wolf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We revisit Max Weber's hypothesis on the role of Protestantism for economic development. We show that nationalism is crucial to both, the interpretation of Weber's Protestant Ethic and empirical tests thereof. For late 19th century Prussia we reject Weber's suggestion that Protestantism mattered due to an "ascetic compulsion to save". Moreover, we find that income levels, savings, and literacy rates differed between Germans and Poles, not between Protestants and Catholics using pooled OLS and IV regressions as well as IV mediation analysis. We suggest that this result is due to anti-Polish discrimination.
Keywords: N13; N33; O16; Z12; 330; Max Weber; Protestantism; Nationalism